IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS IN CHILDCARE CENTRES (TASKA) ALIGNED WITH PARENTAL ASPIRATIONS. - NURUL ZATIE CHE MAT NASIR; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study explores the implementation of teaching and learning approaches for infants and toddlers in Malaysian childcare centres (TASKA) and examines their alignment with the evolving aspirations of modern parents. As parental expectations shift towards holistic child development—encompassing cognitive, emotional, and moral growth—TASKA centres face increasing pressure to adopt pedagogically sound and developmentally appropriate practices. Employing a qualitative library research design, this study synthesises findings from academic literature, policy documents, and government reports published within the last decade. Thematic analysis was used to identify key patterns in pedagogical strategies, parental priorities, and policy frameworks. Findings reveal that while many TASKA centres have embraced play-based and thematic learning approaches, disparities in educator training, resource allocation, and policy enforcement contribute to inconsistent quality. The study highlights the need for standardised teacher training, a unified curriculum for children under four, and stronger collaboration between parents and educators. These recommendations aim to enhance the quality and consistency of early childhood education in Malaysia, ensuring that TASKA centres meet both developmental needs and parental aspirations.